TNF-Mediated Inhibition of Classical Swine Fever Virus Replication Is IRF1-, NF-κB- and JAK/STAT Signaling-Dependent - Matthias Liniger; Markus Gerber; Sandra Renzullo; Obdulio García-Nicolás; Nicolas Ruggli (Viruses, 2021)
The sera from pigs infected with virulent classical swine fever virus (CSFV) contain substantial amounts of tumor necrosis factor (TNF), a prototype proinflammatory cytokine with pleiotropic activities. TNF limits the replication of CSFV in cell culture. In order to investigate the signaling involved in the antiviral activity of TNF, we employed small-molecule inhibitors to interfere specifically with JAK/STAT and NF-κB signaling pathways in near-to-primary endothelial PEDSV.15 cells. In addition, we knocked out selected factors of the interferon (IFN) induction and signaling pathways using CRISPR/Cas9. We found that the anti-CSFV effect of TNF was sensitive to JAK/STAT inhibitors, suggesting that TNF induces IFN signaling. Accordingly, we observed that the antiviral effect of TNF was dependent on intact type I IFN signaling as PEDSV.15 cells with the disrupted type I IFN receptor lost their capacity to limit the replication of CSFV after TNF treatment. Consequently, we examined whether TNF activates the type I IFN induction pathway. With genetically modified PEDSV.15 cells deficient in functional interferon regulatory factor 1 or 3 (IRF1 or IRF3), we observed that the anti-CSFV activity exhibited by TNF was dependent on IRF1, whereas IRF3 was dispensable. This was distinct from the lipopolysaccharide (LPS)-driven antiviral effect that relied on both IRF1 and IRF3. In agreement with the requirement of IRF1 to induce TNF- and LPS-mediated antiviral effects, intact IRF1 was also essential for TNF- and LPS-mediated induction of IFN-β mRNA, while the activation of NF-κB was not dependent on IRF1. Nevertheless, NF-κB activation was essential for the TNF-mediated antiviral effect. Finally, we observed that CSFV failed to counteract the TNF-mediated induction of the IFN-β mRNA in PEDSV.15 cells, suggesting that CSFV does not interfere with IRF1-dependent signaling. In summary, we report that the proinflammatory cytokine TNF limits the replication of CSFV in PEDSV.15 cells by specific induction of an IRF1-dependent antiviral type I IFN response.